Peranan Pusat Pelatihan Pertanian dan Perdesaan Swadaya (P4S) dalam Pemberdayaan Petani di Kabupaten Lampung Timur - Welly Nurul Apreliani; Dewangga Nikmatullah; Helvi Yanfika; Muhammad Ibnu; Tubagus Hasanuddin (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
The role of the Independent Agricultural and Rural Training Center (P4S) is to conduct training and assistance for people who want to learn in the field of superior farming developed by each P4S Institution. P4S has an important role in empowering farmers by providing technical knowledge, access to markets and financial support. The role of P4S is inseparable from internal and external factors of the Institution, so this study aims to determine the factors related to the role of P4S in East Lampung Regency. Internal factors of the Institution are the system of institutional governance, cooperation and partnership, institutional capacity, and management of the Institution. External factors of the Institution are the number of assisted farmers and the reward system. The research was conducted from October to November 2022. The respondents in this study were 70 people who helped farmers assisted by P4S in East Lampung Regency. Data was collected through interview techniques with semi-structured questionnaires—data analysis using path analysis PLS (Partial Least Square) with SmartPLS. The results of this study show that the institutional governance system, institutional capacity, institutional management, and reward system are related to the role of P4S in East Lampung Regency. Institutional governance system, cooperation, and partnerships, the role of P4S associated with the level of empowerment of assisted farmers P4S in East Lampung Regency. Institutional governance system related to direct and indirect empowerment of assisted farmers through the role of P4S in East Lampung Regency. The Institution's governance system was found to be the most important factor related to the role of P4S. A good institutional governance system can help P4S become more effective and efficient in providing training, counselling and assistance to farmers.